Solving the constrained sports event scheduling problem using genetic algorithm as applied to the University of the Philippines Cebu intramural games - Lim, Jon Patrick V. (2014)
Abstract: Sports scheduling is an area of growing interest in computer science. Organizers now prefer automated scheduling, rather than the manual scheduling, because of its efficiency, quickness, and its ability in creating an optimal schedule based on the constraints specified by the user or the sports event. This study explored the use of genetic algorithm (GA) for sports scheduling, specifically for plotting an optimal schedule for the UP Cebu Intramural Games (UPCIG). The idea was to come up with a schedule for UPCIG such that eighty percent (80%) of all the players would have no conflicts with their game schedules. A simple GA was used in solving this problem. An encoding strategy was presented to eliminate all other constraints and concentrate on the player?s conflicting schedules. Measuring the chromosome?s fitness was based on the n number of scenarios specified by the user. Results showed that the algorithm implemented was able to come up with a schedule for the UPCIG with 80 % fitness. The performance (in terms of execution time) of the system greatly depends on the number of scenarios for the fitness function. The system implemented was able to satisfy the constraints for the UPCIG problem and produce a schedule that allowed 80% of players participating in the UPCIG to have no conflicts in the time of their games.